THE IMPACT OF RISING RICE PRICES ON THE INCOME AND WELFARE OF RICE FARMERS IN KLATEN - Sholihah, Efi Nikmatu (Acitya Wisesa: Journal of Multidisciplinary Research, 2025)
Rice is a major food commodity in Indonesia and plays an important role in people's daily lives. The increase in rice prices can have a complex impact on farmers' incomes. Although it sounds like a profitable thing, the increase in rice prices can also mean higher production costs for farmers, such as more expensive fertilizer and seed prices. In addition to having an impact on farmers' income, the increase in rice prices can also affect the economic welfare of farmers. The economic welfare of farmers is not only related to the income earned but also to the farmer's expenses in each harvest period. The study aims to determine the impact of the increase in rice prices on the income and welfare of rice farmers in Klaten. Data collection was carried out using the interview method with rice farmers in the Sri Makmur Dk. Tempel Farmer Group, Jogosetran Village, Kali Kotes, Klaten. Data analysis was conducted by analyzing costs, revenues, income, and welfare analysis by comparing income and expenditure of farmer households. The results indicate that although farmers' income has increased, their welfare has not improved significantly due to rising production and household costs. This study emphasizes the importance of policies that not only regulate commodity prices but also improve production cost efficiency to enhance farmers' welfare.